Development of Internet of Thing (IoT) system for monitoring ruminant grass growth enviroment in vertical farming system - Attirmizi, Zulkifli (2022)
Grassland is the key challenge for small and medium farmers or breeders in Malaysia and other developing nations that want to grow ruminant grass for their ruminants' nourishment. To address these difficulties, an intensive farming system based on a Vertical Farming System (VFS) with a system that can monitor the surrounding environment of the ruminant grass and automate the system is required. The main purpose of this research is to see how well the sensor can integrate soil moisture, pH, humidity, and temperature from the surrounding environment into a vertical system in any situation. This research will take place in December 2021. Three types of sensors were used in this study: capacitive soil moisture, pH, humidity, and temperature sensors. After collecting a large amount of data, especially during daytime, the data analysis on pH, relative humidity and temperature was completed successfully. In the vertical farming system, the repetition of the measurement recorded with the designed error rate function on the sensor helps to limit the risk of soil moisture stress or low pH condition on ruminant grass development (VFS). In the long term, the number of sensors might be raised to offer more data on vertical farming, such as pH, carbon dioxide levels, and air quality. A camera for image processing might also be added. At the same time, crop colour may be evaluated to identify crop quality, and crop height can be measured on a regular basis to estimate plant growth rate.